Análisis descriptivo del estado de salud en un grupo de adultos mayores del Barrio La Primavera, Ibarra - Pozo Flores, Henry Napoleón (2024)
The state of health and well-being of the elderly population is considered a matter of vulnerability, mainly because they are exposed to a series of factors that put their integrity at risk. This research was carried out to describe the health status of older adults in the La Primavera neighborhood. It was a descriptive type of research, with a cross-sectional, non-experimental and field quantitative approach. The sample was selected on the basis of compliance with the inclusion criteria, in order to apply the different tests directed towards the four assessment spheres: clinical, functional, mental and social. The KICA-COG scales were used: Clinical and Cognitive Record, SARCO-GS Scale, Red Cross Scale, Yesavage and Gijon Scale. The results obtained from the research work allowed finding significant data regarding health status, social, functional and cognitive condition. The clinical assessment determined that hypertension is the most prevalent disease with 63% and that the population does not suffer from dementia, but about 32% are likely to suffer from it. The functional assessment found that 94% are independent and 55% have sarcopenia. The mental assessment found that 76% are not at risk of depression. The social sphere showed that 78% are at social risk due to abandonment, loneliness and isolation. It can be concluded that the population is characterized by being independent and with different degrees of alteration in their functions, for which it is advisable to provide adequate support both in prevention and in stimulation of the functions that are notably deteriorated. The Comprehensive Geriatric Assessment as a multidimensional and multidisciplinary instrument determines new findings that help to improve the quality of life of the elderly population.